1984
DOI: 10.1159/000128418
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E<sub>1</sub>Treatment in Experimental Acute Pancreatitis in the Rat

Abstract: Prostaglandin E1 (PGE1) was tested for cytoprotective activity against the development of experimental acute pancreatitis in the rat induced by the closed duodenal loop technique. Sham-operated, untreated and PGE1-treated pancreatitic rats were investigated. All rats received an initial bolus of 3 ml 5% dextrose in normal saline (D5NS) via jugular catheter 30 min prior to surgery, and a continuous subcutaneous infusion of 35 ml D5NS over 24 h. Each treated rat received 10 µg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Recent studies have demonstrated a number of treatments that have an effect on both the course and severity of acute pancreatitis. These include protease inhibitors 131, 132 , trypsin inhibitors 134–136, somatostatin 137 , prostaglandin E 1 138 , vasopressin 139 and dextran 40 140 .…”
Section: Invasive Experimental Modelsmentioning
confidence: 99%
“…Recent studies have demonstrated a number of treatments that have an effect on both the course and severity of acute pancreatitis. These include protease inhibitors 131, 132 , trypsin inhibitors 134–136, somatostatin 137 , prostaglandin E 1 138 , vasopressin 139 and dextran 40 140 .…”
Section: Invasive Experimental Modelsmentioning
confidence: 99%
“…Findings from this model support the hypothesis that reflux of duodenal contents into the pancreatic duct is a possible etiologic factor in the development of acute pancreatitis (Su, Cuthbertson, and Christophi 2006). While ligation of the duodenum is ultimately lethal, the model has efficacy with a number of treatments that affect both the course and severity of the ensuing pancreatitis including the coadministration of protease inhibitors (Murakami et al 1990; Ono et al 1990), somatostatin (De Rai et al 1988), prostaglandin E1 (Crocket et al 1984), and vasopressin (Schapiro et al 1976).…”
Section: Animal Models Of Acute Pancreatitismentioning
confidence: 99%